Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$f(x)$ is three-times differentiable on $[a,b]$, how to show that there is $\varepsilon\in(a,b)$ such that $$f(b)=f(a)+\cfrac{1}{2}(b-a)[f'(a)+f'(b)]-\cfrac{1}{12}(b-a)^3f'''(\varepsilon)$$

share|cite|improve this question
What does three bands derivable mean ? – Amr Feb 5 '13 at 8:09
up vote 5 down vote accepted

Let $$F(x) := f(b)-f(x)- \frac{1}{2} (b-x) \cdot (f'(b)+f'(x)) - K \cdot (b-x)^3$$ where $$K := \frac{f(b)-f(a)-\frac{1}{2} (b-a) \cdot (f'(b)+f'(a))}{(b-a)^3} \tag{1}$$ Then $F$ is differentiable on $[a,b]$ and $F(a)=F(b)=0$. ($K$ is chosen such that $F(a)=0$.) By Rolle's theorem there exists $\varrho \in (a,b)$ such that $F'(\varrho)=0$, i.e.

$$ \begin{align} 0 = F'(\varrho) &= \underbrace{-f'(\varrho)+ \frac{1}{2} (f'(b)+f'(\varrho))}_{\frac{1}{2} (f'(b)-f'(\varrho))}- \frac{1}{2}(b-\varrho) \cdot f''(\varrho) + 3K \cdot (b-\varrho)^2 \\ \Leftrightarrow - \frac{1}{2} f'(b) &= - \frac{1}{2}f'(\varrho) - \frac{1}{2}f''(\varrho) \cdot (b-\varrho) + 3K \cdot (b-\varrho)^2 \tag{2} \\ \Leftrightarrow g(b) &= g(\varrho) + g'(\varrho) \cdot (b-\varrho) +3K \cdot (b-\varrho)^2 \end{align} $$

where $g:=-\frac{1}{2} f'$. This already looks like a Taylor expansion of $g$. In fact, by applying Taylor's theorem to $g$ we obtain

$$\begin{align} g(b) &= g(\varrho) + g'(\varrho) \cdot (b-\varrho) + \frac{g^{(2)}(\varepsilon)}{2!} \cdot (b-\varrho)^2 \\ \Leftrightarrow - \frac{1}{2} f'(b) &= - \frac{1}{2} f'(\varrho) - \frac{1}{2} f''(\varrho) \cdot (b-\varrho) - \frac{1}{2} \cdot \frac{f^{(3)}(\varepsilon)}{2!} \cdot (b-\varrho)^2 \tag{3} \end{align}$$

for some $\varepsilon \in (\varrho,b) \subseteq (a,b)$. Now we subtract $(3)$ from $(2)$:

$$\begin{align} 0 &= 3K \cdot (b-\varrho)^2 + \frac{f^{(3)}(\varepsilon)}{4} \cdot (b-\varrho)^2 \\ \Rightarrow K &= - \frac{1}{12} \cdot f^{(3)}(\varepsilon) \end{align}$$ Hence

$$ \begin{align} - \frac{1}{12} \cdot f^{(3)}(\varepsilon) &= K \stackrel{(1)}{=} \frac{f(b)-f(a)-\frac{1}{2} (b-a) \cdot (f'(b)+f'(a))}{(b-a)^3} \\ \Leftrightarrow f(b) &= f(a) + \frac{1}{2} (b-a) \cdot (f'(b)+f'(a)) - \frac{1}{12} \cdot (b-a)^3 \cdot f^{(3)}(\varepsilon) \end{align}$$

share|cite|improve this answer
Great job, saz, +1. – 1015 Feb 10 '13 at 16:11

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.